DCIS of the breast: The value of preoperative MRI. Issue 2 (25th January 2016) - Doyle, Anthony James; Prakash, Sharath; Wang, Kaye; Cranshaw, Isaac; Taylor, Eletha; Oldfield, Robyn
Abstract: Introduction: Ductal carcinoma in situ (DCIS) of the breast is commonly treated surgically. The intent of this study was to evaluate whether preoperative MRI could add to mammography in predicting the extent of the disease. Methods: A series of patients with DCIS attending our surgical clinic for preoperative assessment were offered MRI as part of a prospective study. The extent of the disease indicated by mammography and MRI was compared with histopathology after definitive treatment. The null hypothesis was that MRI does not add to mammography in accurately predicting disease extent. Results: Fifty patients make up the basis of this report. Mammography was concordant with the pathology in 31/50. MRI and mammography combined were concordant in 43/50. This is a statistically significant difference ( P = 0.01, Fisher's exact test). Upstaging to mastectomy by MRI was correct in 7/8 patients, but downstaging was correct in only 2/4. Conclusions: The null hypothesis is rejected. MRI does add to mammography in accurately predicting the extent of DCIS. Upstaging by MRI is usually reliable.